Transformasi Tata Kelola Koperasi Mahasiswa pada Koperasi Mahasiswa Giri Widya Karta UPN “Veteran” Jawa Timur Periode 2016–2018 - Hutama Muhammad Anhar (J-Coop : Journal of Co-operative, 2026)
This study documents the governance transformation of Kopma GWK (Giri Widya Karta Student Cooperative) at UPN "Veteran" East Java during the 2016–2018 period. Using a qualitative single case study approach with participant observation as the primary data source, the researcher — who served as the cooperative's chairperson during the period — examines how three interrelated challenges were addressed: senior member interference in organizational decision-making, a dysfunctional cadre regeneration system, and the necessity to restructure business units following the university's transition to state institution (PTN) status. The findings reveal that governance transformation was anchored on three strategic pillars: (1) stakeholder boundary management to resolve senior interference through institutional mediation; (2) structured cadre development through benchmarking with established cooperatives and integration into national Kopma networks; and (3) adaptive business model restructuring — resulting in the establishment of KCC (Kopma Copy Center), Kopmart, and general trading units — in response to state asset regulations triggered by a national audit (BPK) finding. These efforts contributed to Kopma GWK receiving the Outstanding Cooperative (Koperasi Unggulan) award from the Surabaya City Cooperative Office in 2017, a recognition unique to Kopma at the time. The study contributes to the literature on cooperative governance and organizational change management in Indonesian higher education institutions, offering a practitioner-informed perspective on sustainable organizational transformation..